1998
DOI: 10.1038/cr.1998.21
|View full text |Cite
|
Sign up to set email alerts
|

The 5′-flanking cis-acting elements of the human ɛ-globin gene associates with the nuclear matrix and binds to the nuclear matrix proteins

Abstract: The nuclear matrix attachment regions(MARs) and the binding nuclear matrix proteins in the 5'-flanking cisacting elements of the human ε-globin gene have been examined. Using in vitro DNA-matrix binding assay, it has been shown that the positive stage-specific regulatory element (ε-PREII,-446bp ~-419bp) upstream of this gene could specifically associate with the nuclear matrix from K562 cells, indicating that ε-PREII may be an erythroidspecific facultative MAR. In gel mobility shift assay and Southwestern blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…We applied an improved method QACT (quantitative associated chromatin trap) to search the spatially associated chromatin fragments with a previously identified MAR element, which locate upstream of HS2 (MAR HS2 ) in K562 cells [29], [30]. The method is based on the recently reported ACT method [12] and could quantitatively identify previously unknown chromatin fragments associated with a given chromatin fragment [31].…”
Section: Resultsmentioning
confidence: 99%
“…We applied an improved method QACT (quantitative associated chromatin trap) to search the spatially associated chromatin fragments with a previously identified MAR element, which locate upstream of HS2 (MAR HS2 ) in K562 cells [29], [30]. The method is based on the recently reported ACT method [12] and could quantitatively identify previously unknown chromatin fragments associated with a given chromatin fragment [31].…”
Section: Resultsmentioning
confidence: 99%
“…13 Using the potential MAR at the 5Ј region of HS2 (HS2-M1, CATTATAATTA-ACTGTTATTTTTTA, located 158 bp upstream of HindIII in the HS2 core) as a DNA probe for EMSA, we observed a slow migrating band from the K562 nuclear extract ( Figure 3B, lanes 1-4). This band was competed by the SATB1-binding sequence Wt (25) 7 ) (S), 17 and by SATB1 antibody (␣S), but not by a mutated SATB1-binding competitor (⌬S), mut (24) 8 (5Ј-(TCTTTAATTTC-TACTGCTTTAGAA) 8 -3Ј).…”
Section: Satb1 Interacts With Mars Localized In the ␤-Globin Cluster mentioning
confidence: 99%
“…[12][13][14][15]42 It has been suggested that SATB1 may participate in a dynamic process to mediate looping of the ␤-globin locus to achieve transcriptional control, advancing the notion that SATB1 binding to MARs may facilitate the remodeling of local chromatin structure and may bring distal regulatory elements in close proximity to promoters. 16 We screened these potential MARs or SATB1-binding regions [12][13][14][15]42 and found that SATB1 bound in vivo to HS2 (M1) and the ⑀-globin promoter M ⑀ , but did not bind to previously reported in vitro binding sites in the 3Ј ␥-globin enhancer or ␤-IVS2 or to ATC sequence-rich regions in HS3, HS4, or the 5Ј region of the ␥-or ␤-globin genes. HS2 was the first hypersensitive site identified in the LCR with erythroid-specific developmental stage-independent enhancer activity 43 and HS2, but not HS3 or HS4, activates transcription of the ⑀-globin gene in K562 cells in studies using chromatinized episomes.…”
Section: Human Primary Erythroid Progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…These elements are not identical but have a number of common properties: they are usually about 1,000 bp or slightly more, are AT-rich, they often form non-canonical DNA structures (palindromes or different distortions of the double helix), are often situated near cisregulatory sequences (enhancers, promotors, insulators, and transcription factor binding sequences) and contain sites or regions hypersensitive to DNAse I. Moreover, MARs are enriched in topoisomerase II cleavage sites [Gasser and Laemmli, 1986;Boulikas, 1993Boulikas, , 1994Bode et al, 1995;Yan and Qian, 1998;Porter et al, 1999;Razin, 2001;Holmes-Davis and Comai, 2002;Felsenfeld et al, 2004;Yusufzai and Felsenfeld, 2004].…”
mentioning
confidence: 98%